Will a plant germplasm accession conserved in a genebank change genetically over time? - Fu, Yong-Bi (Frontiers in Plant Science, 2024)
The simplified question on the genetic change of a conserved plant germplasm accession over time is raised for a better understanding of the challenging mission of conserving more than 7.4 million germplasm accessions in 2000 genebanks worldwide for generations to come. Its answer will influence how these genebanks operate to ensure the continued survival and availability of the conserved plant genetic resources for future food security. Here, we explore the expected impact of evolutionary forces on plant germplasm in genebanks, search for the theoretical expectations and empirical evidence for such impacts from the literature, and discuss the ramifications of the evidence for long-term plant germplasm management and conservation. It is expected that genetic changes of long-term conserved germplasm under genebank conditions will occur commonly as an evolutionary rule, not as an exception. Incorporating evolutionary biology into the Genebank Standards and operational procedures will benefit the mission of long-term germplasm conservation.